Exogenous abscisic acid and sugar induce a cascade of ripening events associated with anthocyanin accumulation in cultured Pinot Noir grape berries - Bennett, Jeffrey; Meiyalaghan, Sathiyamoorthy; Nguyen, Han M.; Boldingh, Helen; Cooney, Janine; Elborough, Caitlin; Araujo, Leandro Dias; Barrell, Philippa; Lin-Wang, Kui; Plunkett, Blue J.; Martin, Damian; Espley, Richard V. (Frontiers in Plant Science, 2023)
Fruit quality is dependent on various factors including flavour, texture and colour. These factors are determined by the ripening process, either climacteric or non-climacteric. In grape berry, which is non-climacteric, the process is signalled by a complex set of hormone changes. Abscisic acid (ABA) is one of the key hormones involved in ripening, while sugar availability also plays a significant role in certain ripening aspects such as anthocyanin production. To understand the relative influence of hormone and sugar signalling in situ can prove problematic due to the physiological and environmental (abiotic and biotic) factors at play in vineyards. Here we report on the use of in vitro detached berry culture to investigate the comparative significance of ABA and sugar in the regulation of Pinot noir berry anthocyanin production under controlled conditions. Using a factorial experimental design, pre-véraison berries were cultured on media with various concentrations of sucrose and ABA. After 15 days of in vitro culture, the berries were analysed for changes in metabolites, hormones and gene expression. Results illustrated a stimulatory effect of sucrose and ABA on enhancing berry colour and a corresponding increase in anthocyanins. Increased ABA concentration was able to boost anthocyanin production in berries when sucrose supply was low. The sucrose and ABA effects on berry anthocyanins were primarily manifested through the up-regulation of transcription factors and other genes in the phenylpropanoid pathway, while in other parts of the pathway a down-regulation of key proanthocyanindin transcription factors and genes corresponded to sharp reduction in berry proanthocyanidins, irrespective of sucrose supply. Similarly, increased ABA was correlated with a significant reduction in berry malic acid and associated regulatory genes. These findings suggest a predominance of berry ABA over berry sugar in coordinating the physiological and genetic regulation of anthocyanins and proanthocyanins in Pinot noir grape berries.